Autism, identity and me : a professional and parent guide to support a positive understanding of autistic identity - Duffus, Rebecca, 1986-; Smith, Beth (Illustrator) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
'This informative and engaging guidebook provides key adults with the tools needed to support children and young people as they develop a positive understanding of their autistic identity. The guidebook is designed to accompany the Autism, Identity and Me workbook, building the adult's understanding of autism and autistic identity, expanding upon the themes introduced, and offering a clear and structured approach to guide the young person through the workbook. Content has been shaped by autistic advisors and contributors, with first-hand experiences woven throughout, alongside examples of'possible prompts', what to focus on as a lead adult, and a variety of concrete, neurodiversity-affirming strategies. Having a positive understanding of your autistic identity is an indicator of higher self-esteem and wellbeing as an adult. This guidebook supports the development of this and will be valuable for all adults working with autistic children and young people aged 10'--
What is autism? -- Emotions, Anxiety & Masking -- Girls -- Debunking Myths -- Using the Workbook -- Section Guidance -- Session 1: Introduction -- Session 2: What autism is -- Session 3: My autism identity : Social and communication -- Session 4: My autism identity : Sensory -- Session 5: My autism identity : Routine and structure -- Session 6: Other autistic individuals.
Includes bibliographical references and index.
Keywords: Autistic children -- Care; Parents of autistic children -- Handbooks, manuals, etc